Delineating the genotypic and phenotypic spectrum of HECW2-related neurodevelopmental disorders. Issue 7 (28th July 2021) - Acharya, Anushree; Kavus, Haluk; Dunn, Patrick; Nasir, Abdul; Folk, Leandra; Withrow, Kara; Wentzensen, Ingrid M.; Ruzhnikov, Maura R. Z.; Fallot, Camille; Smol, Thomas; Rama, Mélanie; Brown, Kathleen; et al.
Abstract : Background: Variants in HECW2 have recently been reported to cause a neurodevelopmental disorder with hypotonia, seizures and impaired language; however, only six variants have been reported and the clinical characteristics have only broadly been defined. Methods: Molecular and clinical data were collected from clinical and research cohorts. Massive parallel sequencing was performed and identified individuals with a HECW2- related neurodevelopmental disorder. Results: We identified 13 novel missense variants in HECW2 in 22 unpublished cases, of which 18 were confirmed to have a de novo variant. In addition, we reviewed the genotypes and phenotypes of previously reported and new cases with HECW2 variants (n=35 cases). All variants identified are missense, and the majority of likely pathogenic and pathogenic variants are located in or near the C-terminal HECT domain (88.2%). We identified several clustered variants and four recurrent variants (p.(Arg1191Gln);p.(Asn1199Lys);p.(Phe1327Ser);p.(Arg1330Trp)). Two variants, (p.(Arg1191Gln);p.(Arg1330Trp)), accounted for 22.9% and 20% of cases, respectively. Clinical characterisation suggests complete penetrance for hypotonia with or without spasticity (100%), developmental delay/intellectual disability (100%) and developmental language disorder (100%). Other common features are behavioural problems (88.9%), vision problems (83.9%), motor coordination/movement (75%) and gastrointestinal issues (70%). Seizures were present in 61.3% of individuals. Genotype-phenotype analysis shows that HECT domain variants are more frequently associated with cortical visual impairment and gastrointestinal issues. Seizures were only observed in individuals with variants in or near the HECT domain. Conclusion: We provide a comprehensive review and expansion of the genotypic and phenotypic spectrum of HECW2 disorders, aiding future molecular and clinical diagnosis and management.